Blood Biochemical Profile In Repeat Breeding Mehsana Buffaloes - Kapadiya, F. M.; Siddiquee , G. M. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Blood biochemical constituents play an important role in maintaining fertility. The biochemical attributes glucose, total protein, albumin and globulin showed noticeable significant increase in treated Group-I (Cephalexin) and Group- II Ciprofloxacin+Tinidazole) as compared to untreated Group-III (control), whereas cholesterol levels were not affected significantly in present study. However the concentration of glucose in blood plasma of Group-III was significantly lower (P
Keywords: Buffalo; Oestrus cycle; Repeat breeder